A Suitability in Assessing PV Potential in UTHM Campus Pagoh Using Homer Simulation - Zulkarnain, Nur Aini (Progress in Engineering Application and Technology, 2023)
The increasing adoption of renewable energy sources, such as photovoltaic (PV) systems, is driven by their ability to reduce reliance on non-renewable energy sources and their environmentally friendly properties. This study aims to evaluate the feasibility of implementing a PV system at the UTHM Campus Pagoh using Homer simulation. A literature review is conducted to gather information on solar panel types, benefits, and factors influencing efficiency. The Homer software helps identify the most cost-effective PV system installation method on campus. Analysis of power consumption data and research findings reveal that a PV system can potentially reduce energy consumption and costs. This significant finding suggests that implementing a PV system at UTHM Campus Pagoh can bring environmental and financial benefits. The study underscores the potential of PV systems as viable and cost-effective solutions for reducing energy consumption and costs in buildings. Further research is needed to explore broader adoption of PV systems.